2014
DOI: 10.1620/tjem.232.47
|View full text |Cite
|
Sign up to set email alerts
|

Improving the One-Year Mortality of Stroke Patients: An 18-Year Observation in a Teaching Hospital

Abstract: Long-term follow-up and comparison of serial changes in the one-year mortality after stroke are important in assessing the quality of stroke management. This study determined the one-year survival rate and prognostic factors of hospitalized hemorrhagic and ischemic stroke patients from 1991 to 2008 in a teaching hospital in Taiwan. We also evaluated the improvements in the one-year mortality after stroke during an 18-year study period. Patients admitted for cerebral hemorrhage (n = 3,678) and cerebral infarcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
1
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 26 publications
3
10
1
9
Order By: Relevance
“…In fact, most frequencies of comorbidities prior to the index event exceeded the rates previously described in previous stroke cohorts [11,12,14,26,27]. A quarter of our patients were classified as having a very severe burden of comorbidities (CCI), which resulted in the maximum mortality risk along the follow-up.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…In fact, most frequencies of comorbidities prior to the index event exceeded the rates previously described in previous stroke cohorts [11,12,14,26,27]. A quarter of our patients were classified as having a very severe burden of comorbidities (CCI), which resulted in the maximum mortality risk along the follow-up.…”
Section: Discussionmentioning
confidence: 58%
“…Two large and more representative population-based studies also revealed positive and consistent findings regarding survival and multimorbidity in stroke populations [11,12]. …”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations